The Application of Ijma' in Islamic Law: Utilizing Zakat, Infaq, and Sadaqah (ZIS) for Humanitarian Crises - Efendi, Nur; Hasan, Mustofa (LAA MAISYIR: Jurnal Ekonomi Islam, 2024)
Humanitarian crises, whether caused by war or natural disasters, often result in victims losing their wealth and becoming poor. Zakat, infak, and sedekah can assist them, but the legal aspects of their utilization must be considered. Zakat can only be given to the eight specified categories. This article aims to explore the use of ZIS for victims of humanitarian crises from the perspective of ijma’. The research method used is a descriptive qualitative approach with library research, which involves collecting data from various sources, followed by data reduction, presentation, conclusion, and data verification. The results of the study show that the use of ZIS for humanitarian purposes is permitted based on the fatwa of the Indonesian Ulema Council (MUI) No. 23 of 2020, No. 66 of 2022, and No. 83 of 2023. These fatwas state that zakat distribution directly to disaster victims must meet the criteria of the eight asnaf. Meanwhile, for public welfare needs, it falls under the asnaf sabilillah. The MUI fatwa can be considered as an ijma’ of Indonesian scholars because its methodology is based on ijma’. However, if the MUI fatwa is not classified as ijma’, it can be considered ijtihad jama’i (collective ijtihad), which represents a consensus of Islamic law experts and other relevant specialists, and its results can be held accountable.